On the "utilization controversy": A rejoinder and some comments - Michalis Nikiforos (Levy Economics Institute of Bard College, 2019)
The critique by Gahn and González (2019) of the conclusions in Nikiforos (2016) regarding what data should be used to evaluate whether capacity utilization is endogenous to demand is weak for the following reasons: (i) The Federal Reserve Board (FRB) measure of utilization is not appropriate for measuring long-run variations of utilization because of the method and purpose of its construction. Even if its difference from the measures of the average workweek of capital(AWW) were trivial, this would still be the case; if anything, it would show that the AWW is also an inappropriate measure. (ii) Gahn and González choose to ignore the longest available estimate of the AWW produced by Foss, which has a clear long-run trend. (iii) Their econometric results are not robust to more suitable specifications of the unit root tests. Under these specifications, the tests overwhelmingly fail to reject the unit root hypothesis. (iv) Other estimates of the AWW, which were not included in Nikiforos (2016) confirm these conclusions. v) For the comparison between the AWW series and the FRB series, they construct variables that are not meaningful because they subtract series in different units. When the comparison is done correctly, the results confirm that the difference between the AWW series and the FRB series has a unit root. (vi) A stationary utilization rate is not consistent with any theory of the determination of capacity utilization. Even if demand did not play a role, there is no reason to expect that all the other factors that determine utilization would change in a fashion that would keep utilization constant.
Keywords: C22; D24; E11; E23; 330; Capacity Utilization; Workweek of Capital; Stationarity